Analysis Of Mathematics Learning Difficulties In Solving Story Problems Based On Newman's Error Analysis - Ashari, Nur Wahidin; Ugi, La Eru; Pakan, Astri Yunianti; Sunardin, Sunardin; Lestari, Wiwit Damayanti (Universitas Wiralodra, 2023)
This study aims to analyze the difficulty of learning mathematics in solving story problems based on Newman's Error Analysis. A total of 22 students were selected by 6 students to be interviewed subjects. The method used in this study is descriptive qualitative with data collection techniques in the form of tests and interviews. Data were analyzed using miles and Huberman data analysis which included data collection, data reduction, data presentation, and conclusion. The results showed that subjects in the high category experienced difficulties at the Transformation, Process Skill, and Encoding stages. Meanwhile, subjects with moderate categories experience difficulties in the Reading, Comprehension, Transformation, Process Skill, and Encoding stages. As well as subjects in the low category also experience difficulties in the Transformation, Process Skill, and Encoding stages.